Fenton and photo-Fenton treatment of a synthetic tannin used in leather tannery a multi-approach study - Lofrano, G (Water science and technology : a journal of the International Association on Water Pollution Research, 2007)
The aim of this work was to compare the behaviour of Fenton and photo-Fenton (UV-A, UV-C) processes to treat synthetic tannin (syntan) used in leather tannery which is one of the most polluting industries, releasing many xenobiotics. Both oxidation processes were performed at pH 3.0 and temperature 40-45 degrees C, which is the original temperature of the re-tanning process, in synthetic solutions containing 100 and 300 mg/L of COD equivalent of syntan. The efficiency of the applied oxidation processes was monitored by chemical oxygen demand (COD), oxidation redox potential (ORP) and aromaticity (UV280) and double bond (UV254) absorbance measurements. Acute toxicity test on Daphnia magna was performed to monitor toxicity in untreated and treated syntan solution. Gas chromatography-mass spectrometry (GC-MS) was applied to identify by-products of partial oxidation occurring in treated samples. The effective ratio of H2O2/FeSO4 for photo-Fenton processes was found to be feasible in terms of reagents used in the process